Dekolonialisasi servant leadership: Karakter, kritik, dan rekonstruksi tata kelola eklesial dalam konteks indonesia - Jonathan Leobisa (KURIOS, 2025)
The "servant leadership" discourse has achieved quasi-dogmatic status in contemporary Christian leadership, yet rarely undergoes critical interrogation of its epistemological assumptions and political implications. This article argues that the uncritical adoption of servant leadership in Indonesian church governance perpetuates colonial patterns through the depoliticization of biblical servanthood, the domestication of service rhetoric that conceals untransformed hierarchical power relations, and the reproduction of Western governance models as universal templates while marginalizing indigenous communal wisdom. Through critical analysis, this study identifies four constitutive characteristics of servant leadership discourse: individualization, moralization, leader-centrism, and ahistoricity. The reconstructive section develops an alternative paradigm of "Participatory-Communal Governance" that integrates early church practices (Acts 2:42-47; 1 Corinthians 12:12-27) with Indonesian indigenous wisdom—gotong royong, tepo seliro, and musyawarah-mufakat—proposing a distributed authority based on charismata, facilitative rotation, and communal deliberation.   Abstrak Diskursus "servant leadership" telah mencapai status quasi-dogmatis dalam kepemimpinan Kristiani kontemporer, namun jarang mengalami interogasi kritis atas asumsi epistemologis dan implikasi politisnya. Artikel ini mengargumentasikan bahwa adopsi tanpa kritik terhadap servant leadership dalam tata kelola gereja Indonesia melanggengkan pola-pola kolonial melalui depolitisasi servanthood biblika, domestikasi retorika pelayanan yang menyembunyikan relasi kekuasaan hierarkis yang tidak tertransformasi, dan reproduksi model governansi Barat sebagai template universal dengan memarjinalkan kearifan komunal indigenous. Melalui analisis kritis, studi ini mengidentifikasi empat karakter konstitutif diskursus servant leadership: individualisasi, moralisasi, leader-sentrisme, dan ahistorisitas. Bagian rekonstruktif mengembangkan alternatif paradigma "Governansi Partisipatif-Komunal" yang mengintegrasikan praktik gereja mula-mula (Kis 2:42-47; 1 Kor 12:12-27) dengan kearifan indigenous Indonesia—gotong royong, tepo seliro, dan musyawarah-mufakat—mengusulkan distribusi otoritas berbasis charismata, rotasi fasilitatif, dan deliberasi komunal.